Incidence And Association Of Generalized Anxiety Disorders In Elderly People With Type 2 Diabetes In Tabuk 2024 - Dr. Sara Abdullah Alfaer,; Dr. Ahmad Raja Albalawi,; Dr. Asma Ali Alharbi,; Dr. Rasha Ali Abdulrahman,; Dr. Marwa Gamal Mohammed,; Dr. Hoda Mohamed El Hady,; Dr. Amal Ali Alharbi, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: A public health concern, GAD is a mental health disorder that frequently affects those with chronic diseases including diabetes. Diabetes and anxiety could pose a double jeopardy of worsening physical health among elderly patients and reducing the quality of life. Especially, since KSA has the highest rate of diabetes worldwide, and it is most notable that the psychological aspect of this disease is not received warmly and is not as researched as it should be, much less is known about the prevalence and effects of GAD among elderly diabetic patients in Tabuk. The purpose of this study is to estimate the incidence of GAD in the elderly patients with T2DM and to analyze the relation between GAD status and glycemic control and diabetic complications. Method: The present study is a descriptive cross-sectional study and took place in January, February, November, and December of 2024 in Tabuk, Saudi Arabia. The sample comprised only outpatients with type 2 DM aged 60 years and older with GAD evaluated through the GAD-7 scale. Participants’ demographic and clinical characteristics were assessed to understand possible correlates of GAD prevalence; glycemic control (HbA1c) and diabetes complications were also compared. Descriptive statistics and chi-square tests were adopted to test the associations of the data collected. Results: It was revealed that 34% of the elderly diabetic patients in Tabuk sampled had GAD with increasing prevalence observed amongst females, long-standing diabetics, and those patients with uncontrolled hyperglycemia. HbA 1c was yet other determinant of the presence and severity of GAD in the study . Also, patients having complications like neuropathy and retinopathy among the diabetic patients also had higher anxiety levels. Conclusion: GAD is evident significantly numerous in elderly having type 2 diabetes in Tabuk and negative correlation existed between anxiety level and glycemic management. By the results of the present study, it can be concluded that the screen of mental health conditions especially anxiety in elderly diabetic patients should be enhanced in order to provide better comprehensive care and health outcomes. According to the study, there is evidence that the enhancement of the targeted interventions aiming at the physical and psychological perspectives for managing combat related diabetes may enhance the quality of life of the clients.